2011
DOI: 10.1177/1090198110372333
|View full text |Cite
|
Sign up to set email alerts
|

Salud America! Developing a National Latino Childhood Obesity Research Agenda

Abstract: U.S. childhood obesity has reached epidemic proportions, with one third of children overweight or obese. Latino children have some of the highest obesity rates, a concern because they are part of the youngest and fastest-growing U.S. minority group. Unfortunately, scarce research data on Latinos hinders the development and implementation of evidence-based, culturally appropriate childhood obesity interventions. In response, the Salud America! network conducted a national Delphi survey among researchers and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 18 publications
0
51
1
1
Order By: Relevance
“…To our knowledge, our study is one of the first studies to examine various types of physician advice among Latino children and their primary caregivers. While our findings support that health care providers offer advice to Latinos [20, 21], rates of advice regarding the amount of screen time and the use of a recreational center are not comparable to rates of advice regarding children's eating habits, weight, and physical activity. Also, findings support that insurance is associated with physician advice, but having private insurance does not appear to guarantee receipt of all types of advice among Latinos [22].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, our study is one of the first studies to examine various types of physician advice among Latino children and their primary caregivers. While our findings support that health care providers offer advice to Latinos [20, 21], rates of advice regarding the amount of screen time and the use of a recreational center are not comparable to rates of advice regarding children's eating habits, weight, and physical activity. Also, findings support that insurance is associated with physician advice, but having private insurance does not appear to guarantee receipt of all types of advice among Latinos [22].…”
Section: Discussioncontrasting
confidence: 86%
“…Nguyen and colleagues [20] found that among a sample of obese Mexican American adults, those who did not receive advice regarding diet and exercise were more likely be younger, speak Spanish at home, lack insurance, and possess lower levels of educational attainment. Conversely, Lopez-Quintero et al [21] found that age was not associated with receipt of physician advice regarding physical activity and diet among adult Latinos with chronic disease. However, English-proficient adults were more likely to receive advice than their limited English-proficient counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of the large increase in obesity research over the last two decades, very few studies have focused on the Latino population [11]. The lack of data on Latinos is an obstacle for the development and implementation of relevant prevention programs [12]. …”
Section: Discussionmentioning
confidence: 99%
“…A socioecological perspective emphasizes the interconnectedness of systems; the relationships between child physical activity, diet, and weight status are nested within the parent, home, and cultural environment. Furthermore, family has been identified as the foremost ecological level in which to prevent Latino child obesity (47). SCT provided a framework to explain why individuals develop and maintain health behaviors, and how these learned behaviors are influenced by the individual’s environment and self-efficacy.…”
Section: Methodsmentioning
confidence: 99%